Prilaku Proses Berpikir Menyelesaikan Geometri Pada Konteks Bahasa: Verbalization, Self-Explanation, Oral Description - Lutfiyah Lutfiyah; Susanto Susanto; Abi Suwito (Universitas Islam Jember, 2026)
This study aims to describe students’ thinking processes in solving geometry problems through verbal expressions: verbalization, self-explanation, and oral description. The participants were three university students who were asked to work on geometry tasks containing linguistic descriptions. Data were collected through video recordings, students’ written solutions, and think-aloud notes capturing their thinking processes. Data analysis followed three stages: data reduction, data display, and conclusion drawing. The results show that all participants demonstrated strong verbalization skills by restating key information from the problem text and representing it through labels and annotations in their drawings. In the self-explanation aspect, the three students attempted to justify their solution steps through sequences of calculations, although the strategies they used were not entirely accurate. Regarding oral description, all participants were able to describe the triangle structure, point positions, and altitude lines, yet not all of them could consistently connect these visualizations with correct computational procedures. These findings affirm that students’ verbal expressions play an important role in revealing the structure of their thinking processes, especially in geometry problems that require integration between linguistic descriptions and spatial representations. Keywords: Thinking Process, Geometry, Verbalization, Self-Explanation, Oral Description